A Role for Nitric Oxide in the Development of the Ferret Retinogeniculate Projection - Cramer, Karina S. (J Neurosci, 1996)
The ferret retinogeniculate projection segregates into eye-specific layers during the first postnatal week and into ON/OFF sublaminae, which receive inputs from either on-center or off-center retinal ganglion cells, during the third and fourth postnatal weeks. The restriction of retinogeniculate axon arbors into eye-specific layers appears to depend on action potential activity (Shatz and Stryker, 1988) but does not require activation of NMDA receptors (Smetters et al., 1994). The formation of ON/OFF sublaminae is also activity-dependent and is disrupted by in vivo blockade of NMDA receptors (Hahm et al., 1991). To investigate a possible mechanism whereby blockade of postsynaptic NMDA receptors in the lateral geniculate nucleus (LGN) results in changes in the size and position of presynaptic axon arbors, we tested the role of the diffusible messenger nitric oxide (NO) in the development of the retinogeniculate pathway. We found previously that NO synthase (NOS) is transiently expressed in LGN cells during the refinement of retinogeniculate projections (Cramer et al., 1995). In this study, treatment with N(G)-nitro-l-arginine (l-NoArg), an arginine analog that inhibits NOS, during the third and fourth postnatal weeks resulted in an overall pattern of sublamination that was significantly reduced compared with normal and control animals. Single retinogeniculate axon arbors were located in the middle of eye-specific layers rather than toward the inner or outer half as in normal or control animals. The effect of NOS inhibition was not a consequence of the hypertensive effect of l-NoArg. In contrast to the effect of l-NoArg on the formation of ON/OFF sublaminae, treatment with l-NoArg during the first postnatal week did not disrupt the formation of eye-specific layers. Biochemical assays indicated significant inhibition of NOS during both treatment periods. These data suggest that NO acts together with NMDA receptors in activity-dependent refinement of connections during a specific phase of retinogeniculate development.